AhR activation mitigates graft-versus-host disease of the central nervous system by reducing microglial NF-κB signaling - Zähringer, Alexander Johannes; Morgado, Inês; Erny, Daniel; Ingelfinger, Florian; Gawron, Jana; Chatterjee, Sangya; Wenger, Valentin; Schmidt, Dominik; Schwöbel, Lennard; Adams, Rachael C.; Langenbach, Marlene; Hartmann, Alina; et al. (Blood advances, 2025)
Acute graft-versus-host disease (GVHD) that occurs after allogeneic hematopoietic cell transplantation (allo-HCT) can affect the central nervous system (CNS). Most patients who have undergone allo-HCT receive antibiotic treatment, which alters the microbiome and essential microbiome-derived metabolites. We investigated the impact of microbiome modifications on CNS GVHD and therapeutic strategies to overcome the microbiome-derived metabolite depletion. Antibiotic treatment of mice undergoing allo-HCT increased microglia numbers in the brain, indicating increased inflammation. In addition, microglial morphology shifted toward a highly branched phenotype. Consistent with a proinflammatory phenotype, the microglia exhibited increased NF-κB and Src activity. Antibiotic treatment caused the depletion of the bacteria-derived aryl hydrocarbon receptor (AhR) ligand indole-3-acetate in the brain. Conversely, treatment of the primary microglia with the AhR ligand 6-formylindolo(3,2-b)carbazole (FICZ) reduced NF-κB activity and phagocytic potential. Microglia expansion and morphological changes were reversed by AhR ligand FICZ treatment. Moreover, the AhR ligand indole-3-acetate was also reduced in the CNS of patients who developed acute GVHD concomitant with increased microglial NF-κB expression. In summary, we demonstrated that antibiotic treatment and a subsequent decrease of AhR ligands resulted in increased microglial activation in CNS GVHD. FICZ treatment hampered CNS inflammation by inhibiting NF-κB activity, thereby providing a metabolic modifier to interfere with pathogenic microglia signaling and CNS GVHD in vivo.
Veröffentlicht: 12. Juni 2025
Gesehen am 06.11.2025